Handbook of Clinical Nutrition and Aging - Bales, Connie Watkins; Locher, Julie L.; Saltzman, Edward (Nutrition and Health, 2015)
This is the new and fully revised third edition of the well-received text that is the benchmark book in the field of nutrition and aging. The editors (specialists in geriatric nutrition, medical sociology, and clinical nutrition, respectively) and contributors (a panel of recognized academic nutritionists, geriatricians, clinicians, and other scientists) have added a number of new chapters and have thoroughly updated the widely acclaimed second edition. This third edition provides fresh perspectives and the latest scientific and clinical developments on the interaction of nutrition with age-associated disease and provides practical, evidence-based options to enhance this at-risk population's potential for optimal health and disease prevention. Chapters on a wide range of topics, such as the role of nutrition in physical and cognitive function, and coverage of an array of clinical conditions (obesity, diabetes, heart failure, cancer, kidney disease, osteoporosis), compliment chapters on food insecurity, anti-aging and nutritional supplements, making this third edition uniquely different from previous editions. Handbook of Clinical Nutrition and Aging, Third Edition, is a practical and comprehensive resource and an invaluable guide to nutritionists, physicians, nurses, social workers and others who provide health care for the ever-increasing aging population.